Effect of alkaline earth on decay time of Dy3+ doped in Li2O-B2O3 glasses using pulse X-ray excitation. (2019) - Damdee, B.; Kaewkhao, J.; Kirdsiri, K.
Abstract: Different types of alkaline earth lithium borate glasses doped with 0.5 mol% of Dy 3+ ions in composition of 50Li2 O:20MO:29.5B2 O3 :0.5Dy2 O3 (where MO = MgO, CaO, SrO and BaO) were prepared by normal melts quenching technique. The as-prepared glasses were characterized by the density, the optical transmission spectra, and together with decay time under X-ray pulse excitation. With increasing of the molecular weight of alkaline earth oxides the density of glasses increased and the same trend has been observed for the molar volume. The transmission spectra in the wavelength region of 350-2500 nm showed the f - f excitations for Dy 3+ ions from ground states 6 H15/2 to other excited states 6 F5/2, 6 F7/2, 6 F9/2, 6 H7/2, ( 6 F11/2, 6 H9/2 ) and 6 H11/2 . Moreover, a large increase in decay time under pulse X-ray excitation with the larger size of alkaline earth cation have been observed.